Kepemimpinan Di Era Milenial Ditinjau dari Aspek Komunikasi - Hasril Atieq Pohan (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2019)
leadership is one of the keys to success that has a role in achieving organizational goals. The quality of the leader is considered as a factor in the success or failure of an organization. Becoming an effective leader in millennial generation is a tough challenge. Millennial generation is closely related to information and digital communication. So that the communication used develops according to need. The presence of technology in communication makes a change from conventional to digital. This must be a concern by a leader so that as a leader is able to provide spirit and encouragement to millennials in the right way. The research method used is a library reseach that discusses leadership, communication, and millennial generation. Leaders in the millennial era must be trendsetters, they must be able to support millennial generate.ons in order to be innovative and creative and have an entrepreneurial spirit